Counter-hegemonic narratives: from conferences-concerts to plays-lectures (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article takes a look at the conferences-concerts held by the abolitionist movement, in sessions that involved political speeches, theater, music and the handing out of letters of freedom. Organized to raise money for the liberation of enslaved people, the matinees mobilized thousands of people and reflected an intersection between politics and art at the end of the 19th century. The study brings this model closer to today's lecture plays, in which political issues are put on stage using the body and the real. To this end, dramaturgies by two contemporary authors, Rafael Cristiano and Clayton Nascimento, who rework the lecture format in their work from an Afrocentric perspective, are used.
Keywords: abolitionist theater; black theaters; contemporary dramaturgy; theater history; cultural hegemony